Intersecting Identities and Racial Realities: A Comprehensive Study of the Depiction of Racism in Damon Galgut Fictional Narratives - Fajar Rashid; Dr Kulbhushan Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study delves into the intricate depiction of racism within Damon Galgut's fictional narratives, exploring how intersecting identities and racial realities are portrayed in his works. He navigates the complex socio-political landscape of post-apartheid South Africa, shedding light on the enduring impact of racial discrimination and prejudice. Through a comprehensive analysis of his novels, this study examines how he portrays the intersections of race, identity, and power, revealing the nuanced and often subtle manifestations of racism in a society grappling with its historical legacy. By focusing on character development, narrative structure, and thematic content, the research seeks to uncover his fiction which not only reflects the complexities of racial relations but also challenges the reader to confront the uncomfortable truths about inequality and social justice in contemporary South Africa. This study contributes to a deeper understanding of how literature can serve as a powerful tool in examining and critiquing the persistent racial divides in a society striving for reconciliation and equality. By highlighting the intersectionality of race with other aspects of identity, such as gender, class, and sexuality, this study underscores the multifaceted nature of oppression and discrimination that Galgut intricately weaves into his storytelling. Furthermore, the study engages with the broader literary and historical contexts in which the portrayal of racism dialogues with the works of other South African writers and the larger discourse on postcolonial identity. The study also considers the use of narrative techniques, such as shifting perspectives and fragmented timelines, which serve to disrupt traditional notions of history and memory, offering a more complex and layered understanding of the racial realities in South Africa.
Keywords: Realities; Racial Identities; Post-Apartheid; Social Justice; Postcolonial Perspectives.